The Bloomsbury introduction to adaptation studies : adapting the canon in film, TV, novels and popular culture - Griggs, Yvonne (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2016)
From David Lean's big screen Great Expectations to Alejandro Amenabar's reinvention of The Turn of the Screw as The Others, adaptations of literary classics are a constant feature of popular culture today. The Bloomsbury Introduction to Adaptation Studies helps students master the history, theory and practice of analysing literary adaptations. Following an introductory overview of major debates and concepts, each chapter focuses on a canonical text and features: - Case study readings of adaptations in a variety of media, from film to opera, televised drama to animated comedy show, YA fiction to novel/graphic novel. - Coverage of popular appropriations and re-imaginings of the text. - Discussion questions and creative exercises throughout to guide students through their own analyses. - Annotated guides to further reading and viewing plus online resources. - The book also includes chapter overviews and a glossary of critical terms to give students quick access to key information for further study, reference and revision. The Bloomsbury Introduction to Adaptation Studies covers adaptations of: Jane Eyre; Great Expectations; The Turn of the Screw; The Great Gatsby.